Bird communities of the Arctic shrub tundra of Yamal: habitat specialists and generalists - Sokolov, Vasily; Ehrich, Dorothee; Yoccoz, Nigel; Sokolov, Alexander; Lecomte, Nicolas (PLoS ONE, 2012)
The ratio of habitat generalists to specialists in birds has been suggested as a good indicator of ecosystem changes due to e.g. climate change and other anthropogenic perturbations. Most studies focusing on this functional component of biodiversity originate, however, from temperate regions. The Eurasian Arctic tundra is currently experiencing an unprecedented combination of climate change, change in grazing pressure by domestic reindeer and growing human activity. Here we monitored bird communities in a tundra landscape harbouring shrub and open habitats in order to analyse bird habitat relationships and quantify habitat specialization. We used ordination methods to analyse habitat associations and estimated the proportions of specialists in each of the main habitats. Correspondence Analysis identified three main bird communities, inhabiting upland, lowland and dense willow shrubs. We documented a stable structure of communities despite large multiannual variations of bird density (from 90 to 175 pairs/km2). Willow shrub thickets were a hotspot for bird density, but not for species richness. The thickets hosted many specialized species whose main distribution area was south of the tundra. If current arctic changes result in a shrubification of the landscape as many studies suggested, we would expect an increase in the overall bird abundance together with an increase of local specialists, since they are associated with willow thickets. The majority of these species have a southern origin and their increase in abundance would represent a strengthening of the boreal component in the southern tundra, perhaps at the expense of species typical of the subarctic zone, which appear to be generalists within this zone.